when sound becomes an image: picturing oṃ in jainism - gough, ellen (Material religion, 2021)
What happens when a sound becomes an image? This article provides one answer to this question by examining visual representations of the sacred syllable oṃ in Jain ritual culture. Oṃ rose to prominence in Vedic texts from the first millennium BCE as a powerful sound that could ensure the success of the fire sacrifice, but Jain ascetics, who established their tradition around the fifth century BCE, rejected the violence of the sacrifice and the superiority of brahmins. Jains therefore used visual representations of the syllable to distance themselves from brahminical ideology and to focus on oṃ as an icon – a site of divine presence – of the ideal objects of Jain worship, the five supreme beings (pañcaparameṣṭhin). Since images can, at times, more immediately convey ideologies than alinguistic sounds, Jains from the medieval period to the present day have used visualizations, paintings, sculptures, and diagrams inscribed with mantras (yantra) to present the syllable as a representation of the Jain ascetic path to liberation.